Hot topics in football medicine (ASPETAR Sports Medicine Journal, 2021)
An introduction to key issues in footballer welfare Hey coach/doctor/physio/ podiatrist/dad/mum: what football boot is best for me"? Imaging in football medicine Insertional achilles tendon conditions in football referees Hamstring injury Groin injuries in football Mental health symptoms in professional football Concussion care in football